Jenis, Pengaruh, dan Permasalahan dalam Modernisasi Pembelajaran Tematik Sekolah Dasar dengan Pemanfaatan Media Pembelajaran Digital: Penelitian - Rifqa Elvi Mufida; Anita Dwi Lestari; Al Hikmah; Marsa Amalia Rosita; Taufik Muhtarom (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to comprehensively examine the types of digital learning media used in thematic learning at the elementary school level, evaluate their impact on students’ participation and learning interest, and analyze the challenges in their implementation. Using a Systematic Literature Review (SLR) approach guided by the PRISMA protocol, more than 20 scholarly articles published between 2017 and 2025 were analyzed. The findings reveal that digital media such as Canva, PowerPoint, Quizizz, Google Classroom, e-Modules, Android-based applications (Smart Apps Creator, Quizland), digital booklets, and learning management platforms like Kahoot and Moodle have contributed to increasing students' engagement, conceptual understanding, and the effectiveness of formative assessments. However, obstacles remain, including low digital literacy among teachers, limited infrastructure, and the lack of pedagogical ICT training. This study highlights the need for systemic support through continuous teacher training, equitable access to technology, and the development of localized digital content as strategies for sustainable integration. The use of digital media in thematic learning should not be viewed merely as a technical shift, but rather as a transformative step toward a more collaborative, contextual, and creative educational paradigm in the digital age.